2020
DOI: 10.1103/physrevb.102.045131
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior for point monopole and dipole electric impurities in uniformly and uniaxially strained graphene

Abstract: We revisit the problem of bound states in graphene under the influence of point electric monopole and dipole impurity potentials extended to the case in which the membrane of this material is uniformly and uniaxially strained, which leads to a redefinition of the charge and dipole moment, respectively. By considering an anisotropic Fermi velocity, we analytically solve the resulting Dirac equation for each potential. We observe that the effect of the anisotropy is to promote or inhibit the critical behavior kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…To solve the Dirac equation ( 15) for a massless particle, we first decouple the system of equations that the components of Ψ 0,n = (ψ + 0,n , ψ − 0,n ) T fulfill, see Eqs. ( 18) and (19). Both components satisfy the Schrödinger Eqs.…”
Section: Example: Graphene In a Hyperbolic Magnetic Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the Dirac equation ( 15) for a massless particle, we first decouple the system of equations that the components of Ψ 0,n = (ψ + 0,n , ψ − 0,n ) T fulfill, see Eqs. ( 18) and (19). Both components satisfy the Schrödinger Eqs.…”
Section: Example: Graphene In a Hyperbolic Magnetic Barriermentioning
confidence: 99%
“…To confine or control the charge carriers in a graphene sample, electromagnetic fields have to be applied [11][12][13][14]; it has been shown that mechanical deformations can be used as well for that purpose [15][16][17][18][19]. To explore and enrich the configurations where the Dirac equation can be solved exactly (or quasiexactly), supersymmetric quantum mechanics have been used from different approaches [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most experimental and theoretical works have focused on understanding the properties of pristine tBLG, but it is well known that defects play an important role in real devices that exploit the properties of two-dimensional (2D) materials 11,32 . In particular, impurities that donate electrons or holes can be used to control the concentration of charge carriers [33][34][35][36][37][38][39] . Once ionized, these impurities act as Coulomb scatterers and reduce the charge carrier mobility 40 .…”
Section: Introductionmentioning
confidence: 99%